Factors Predicting outcome of patients with polytrauma in tertiary center of western Nepal (Journal of Brain and Spine Foundation Nepal, 2021)
Introduction: Trauma is a public health issue associated with substantial socioeconomic impacts and major adverse clinical outcomes. No single study has previously investigated the predictors of mortality in a general trauma population. In this study, we assessed different clinico-biochemical parameters to investigate the associations between those parameters and their effects in outcome of a polytrauma patient.Methods: An analytical study was done in between January 2020 to December 2020 in patients with polytrauma admitted to intensive care unit Department of Surgery in Manipal Teaching Hospital to assess the effect of various socio-demographic and clinic-radiologic variables in outcome (Glasgow outcome scale) of polytrauma patients. All the categorical data were tested using chi square test or Fischer Exact test and continuous variables were tested using student’s “t” test. P value